HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEKAMBUHAN PADA PASIEN SCHIZOPHRENIA DI POLIKLINIK JIWA RSUD CIDERES KABUPATEN MAJALENGKA TAHUN 2024 - Eti Rohayati, (JURNAL PENGABDIAN MANDIRI, 2025)
Introduction. Based on data from Cideres Hospital, Majalengka Regency, the number of outpatient visits at Cideres Hospital, Majalengka Regency in 2023, schizophrenia is the disease most frequently suffered by patients, namely 674 cases. Other diseases such as anxiety disorders with 161 cases, mental retardation with 112 cases and nonorganic insomnia with 25 cases. Objective. To determine the effect of support on recurrence in schizophrenia patients in the Psychiatric Polyclinic of Cideres Regional Hospital, Majalengka Regency in 2024. Type of research. This research uses a descriptive method. According to Notoatmodjo (2020), descriptive research is research carried out with the main aim of producing an objective influence or description of a situation. The sample in this study was 97 Schizophrenia Patients in the Mental Polyclinic of Cideres Regional Hospital. Data analysis used univariate and bivariate analysis with frequency distribution. Research Results Less than half (36.1%) of schizophrenia patients received insufficient family support at the Polyclinic of Cideres Regional Hospital, Majalengka Regency in 2024. Less than half (32.0%) of schizophrenia patients received inadequate family support in the Cideres Regional Hospital, Majalengka Regency Polyclinic. In 2024. There is a significant relationship between family support and recurrence in Schizophrenia patients in the mental health clinic at Cideres Regional Hospital, Majalengka Regency. In 2024, the p value = 0.006. Suggestion. The hospital, through health workers, should provide information and counseling to schizophrenia patients regarding the treatment that schizophrenia patients must undergo to speed up the healing process and the need to provide education to the patient's family about family support to prevent the risk of relapse in schizophrenia patients